Influence of different media on spawn production of blue oyster mushroom (Hypsizygus ulmarius (Bull.:Fr.) Redhead) - I, SUMI; D, Geetha (Mushroom Research, 2017)
Abstract: Blue oyster mushroom (Hypsizygus ulmarius (Bull.:Fr.) Redhead) is a novel species resembling the common oyster mushroom, but it is far better in flavour and texture than the commonly cultivating oyster mushroom, Pleurotus florida. A study conducted to evaluate the different substrates for the production of good quality spawn for the profitable cultivation of blue oyster mushroom indicated paddy grains as the best spawn media for H. ulmarius with thick and fluffy mycelial growth. Rubber saw dust recorded maximum time (31.75 days) for completing the spawn run and it recorded maximum keeping quality of 104.30 days. Least contamination was recorded in sorghum spawn (10%) followed by paddy grains (20%).